Officer career management additional steps toward modernization - Robbert, Albert A. 1944-; Lee, Caitlin ca. 20./21. Jh; Waggy, William H. ca. 20./21. Jh; Kidder, Katherine L. ca. 20./21. Jh; Lander, Natasha ca. 20./21. Jh; Schaefer, Agnes Gereben (Rand National Defense Research Institute, 2021)
With military departments becoming increasingly interested in modernizing officer career management, the Office of the Secretary of Defense (OSD) requested a study concerning legislative, policy, fiscal, and financial limits on various reforms. These reforms fall into three broad categories: promotions, tenure, and other issues. Promotions involve such issues as alternatives for technical-track career paths, possibilities for different competitive categories to have different promotion rates and frequency, policies to ensure that officers who opt out of promotion consideration are not adversely affected at future statutory boards, the pros and cons of a return to permanent and temporary promotions, and guidance regarding deployability. Tenure issues concern stagnant officers, removal of age limits for accessions, and contractual arrangements for officers. Other issues include providing for a continuum of service among active and reserve personnel, the use of warrant officers and limited duty officers in all the services, and the selective use of "officers without rank." In all cases, another important consideration concerns limits on the scale and timing of reforms to ensure that desired outcomes, measures of effectiveness, and results of the changes can be clearly identified, documented, and leveraged over time. In general, the authors find that an incremental approach that scales the reforms to small populations (at least initially) and avoids implementation of more than one reform at a time could eventually add considerable flexibility to the officer career management structure
Prepared for the Office of the Secretary of Defense, approved for public release; distribution unlimited
Keywords: Offizier; Karriere; USA; United States / Armed Forces / Promotions / Evaluation; United States